SIMBOLISME PATUNG LORO BLONYO - Edy Tri Sulistyo; Jamal Wiwoho (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2008)
The objectives of research are to find out: (1) the cosmology form ofÂ loro blonyoÂ sculpture in Javanese cultural context, (2) placement system of loro blonyoÂ sculp- ture in Â â€œjogloâ€Â house structure relating to the concept of Javanese social-cultural environment Â balance, (3)Â loro blonyoÂ sculpture as the most important element in its position in Â â€œpasrÃ¨nâ€Â room in Javanese custom house, and (4) the symbolic- philosophical meaning ofÂ loro blonyoÂ sculpture art in Javanese cultural cosmology. Based on the result of Â research and discussion, it can be concluded: (1) The cos- mology form ofÂ loro blonyo Â sculpture in the Javanese cultural context relating to the Javanese society particularly the one with rice planting as the earning; (2) The placement system ofÂ loro blonyoÂ sculture in theÂ â€œjogloâ€Â house structure relating to the concept of Javanese social-cultural environment balance; (3)Â Loro blonyoÂ sculp- ture is the most important element in its position in theÂ â€œpasrÃ¨nâ€Â room in Javanese custom house;.Â  Â (4) The symbolic-philosophical meaning of Â loro blonyoÂ sculpture art in Javanese cultural cosmology is as the symbol of fertility (Dewi Sri) and pros- perity (Sadana).Key words:Â loro blonyo, krobongan, pasrÃ¨n or petanÃ¨n, joglo, Dewi Sri, Sadana.